(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background and objective: This study was aimed to determine the effect of addition of 3% of Magnesium Oxide Nanoparticles (MgONPs) on the surface hardness (SH) and tensile bond strength (TBS) of asilicone based denture liner at various time intervals. Method: The SH and TBS of a silicone denture liner were studied after addition of 3% by weight of MgONPs. A total of 140 samples were constructed. The samples were divided into two main groups, control group and test group to which 3% of MgONPs were added. Results: The SH of all the samples for both groups was significantly higher after a period of 6 months. For TBS the pattern was reversed in which there was a decrease in the mean of TBS for both control and test groups significantly. Conclusion: The addition of 3%(MgONPs) to Silicone denture liner causes a non significant effect in the SH but significantly improves TBS.